Urban Air Pollution Control Caused by Exhaust Gas Emissions in Developing Country Cities in Public Policy Law Perspective - Purwadi, Ari; Suhandi, Suhandi; Enggarsasi, Umi (International Journal of Energy Economics and Policy, 2019)
The increase in air pollution in cities generally comes from motor vehicle emissions. The purpose of this paper is to analyze the regulation and role of the city government through public policy to control air pollution. The regulation of air pollution control with legislation has regulated fuel standards, air capacity, negative impacts on the environment due to the use of space, and the exhaust emission threshold. Interrelated planning and regulatory actions can lead to significant reductions in pollutants that change the climate. Public policy regarding air pollution control by the city government is accommodated by the application of the principle of decentralization through regulation. The city government formulates public policies to improve the ability of the community to avoid air pollution and reduce damage to public health caused by air pollution, as well as carry out activities in planning, controlling, and controlling air environmental policy programs that lead to achieving environmental quality. Keywords: air pollution, public policy, pollution control, urban management JEL Classifications: Q52, Q53, K32 DOI: https://doi.org/10.32479/ijeep.8337